PAPR and BER analysis of mobile WiMAX system using QC-LDPC code with STFBC MIMO OFDMA system / Siti Nor Hasima Mat Jusoh - Mat Jusoh, Siti Nor Hasima (2014)
This proposal focus on the Quasi Cyclic Low Density Parity Check (QC-LDPC) Code is a one of the important technique to minimize Power-Average-Power-Ratio (PAPR) and measure bit error rate (BER) performance for the Space-Time Frequency Block-Codes(STFBC) MIMO-OFDMA system. QC-LDPC code consists of small square blocks characterized by the parity-check matrix where required memory can be extensively reduced with the circulant permutation matrix or zero matrix as compared with the randomly that was constructed in earlier LDPC codes. The performance of QC-LDPC Code will evaluate by using diversity technique to maximize achievement of diversity order system. A variety of diversity techniques are used in MIMO-OFDMA system in order to combat the effect of channel fading and improve the system performance. Th e main diversity type is space, time and frequency. MATLAB software is use to develop new Quasi Cyclic LDPC block code algorithm and determine PAPR reduction for the STFBC MIMO-OFDMA system. This propose of coding technique with diversity technique is able to achieve maximum of diversity system. The main goal of fourth generation (4G) wireless communication is to improve network efficiency and increase the link throughput. MIMO wireless systems with OFDMA modulation have a great potential to provide desired performance for the future product development in broadband wireless communication system.